53.0k views
3 votes
Natalie tried to evaluate the expression \left( 4^{-3} \cdot 2^{-3} \right)^{0}(4 −3 ⋅2 −3 ) 0 left parenthesis, 4, start superscript, minus, 3, end superscript, dot, 2, start superscript, minus, 3, end superscript, right parenthesis, start superscript, 0, end superscript. \begin{aligned} &\phantom{=}\left( 4^{-3} \cdot 2^{-3} \right)^{0} \\\\ &=\left( 8^{-3}\right)^{0} &\text{Step } 1 \\\\ &= 8^{0} &\text{Step } 2 \\\\ &=0&\text{Step } 3 \end{aligned} ​ =(4 −3 ⋅2 −3 ) 0 =(8 −3 ) 0 =8 0 =0 ​ Step 1 Step 2 Step 3 ​ Did Natalie make a mistake? If so, in which step?

User Alex Lande
by
5.3k points

2 Answers

6 votes

Answer:

d

Explanation:

User Ioan M
by
4.5k points
3 votes

Given:

The expression is


\left( 4^(-3) \cdot 2^(-3) \right)^(0)

To find:

The Natalie's mistake.

Solution:

We have,


\left( 4^(-3) \cdot 2^(-3) \right)^(0)

Using properties of exponents, we get


=\left( (4* 2)^(-3) \right)^(0)
[\because a^mb^m=(ab)^m]


=\left( (8)^(-3) \right)^(0)


=\left( 8 \right)^(0)
[\because (a^m)^n=a^(mn)]


=1
[\because a^0=1,\text{ where, a is any non zero number}]

Therefore, Natalie make a mistake in Step 3. She write
8^0=0 instead of
8^0=1.

User Endunry
by
4.9k points